Dysmorphic Disorder to Anxiety Career Vocational school students - Dzilan Asyifah; Yuda Syahputra; Rosada Rosada (Psychocentrum Review, 2025)
This study was conducted to investigate the extent to which Body Dysmorphic Disorder (BDD) contributes to career anxiety among students at Mardhika Vocational School. A quantitative correlational approach was applied, with simple linear regression used to examine the influence between the variables. The study involved 110 eleventh-grade students who were selected through random sampling. The findings revealed that BDD significantly influences students’ career anxiety, indicating that higher levels of BDD are associated with greater anxiety about future career choices. The study also identified social media exposure, social pressure, and family expectations as factors that may intensify the effects of BDD on students’ career readiness. These findings highlight the importance of comprehensive and preventive Guidance and Counseling (GC) services in addressing body image concerns and career-related anxiety simultaneously, thereby supporting students in developing healthier self-perceptions and better career readiness.